The fundamentalist term is the license of Ibn Ashour through his book The Purposes of Islamic Law - ben Ali, Abdelkader Hacini; ben El Mabrouk, Achour Boukalkoula (Journal of Islamic Sciences, 2019)
The term "interest" is a very precise term in the proposition. There is a lot of talk about it from a variety of fields. This is due to the difference between the field of jurisprudence and the field of jurisprudence. Through the employment of Imam Muhammad al- Taher Ibn Ashour in his book Makassed Islamic law, as a study of terminology; from the linguistic structure that form the term, until the semantic development of the term, through the functional use of the term when the son of Ashour.